Reading Strategies Used by 12 Graders in an EFL Context: A Correlational Study - Sunggingwati, Dyah; Ungau, Septiwin (TLEMC (Teaching and Learning English in Multicultural Contexts), 2023)
This correlation study investigates three major strategies of cognitive, metacognitive, and socio-affective as the strategies that are generally applied in reading comprehension and reading achievement at secondary level in Indonesia. The participants were 127 of 12 graders. The reading strategy questionnaire adopted from Strategy Inventory for Language learning (SILL, ESL/EFL version 7.0) and reading comprehension test were the used instruments. Using one-way analysis of variance, the results reveal that there was significant correlation of metacognitive strategies and reading comprehension achievement but not with cognitive and socio-affective strategies. In addition, metacognitive was the most frequent strategies employed to reading comprehension.Keywords: reading strategies, comprehension, secondary level